PEMANFAATAN IMAGE TO SPEECH BERBASIS ANDROID UNTUK PENGENALAN WARNA BAGI ANAK BAWAH TIGA TAHUN (BATITA) - Wintolo, Hero; Widiastuti, Anggit Tri (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2015)
The introduction of color to children under three years of age is done by providing and explaining objects favored by children, such as toys and food, which have certain colors so that children recognize colors at that age. Unlike adults, how to introduce color in children does require a different way, in addition to the objects and food, in this study the introduction of color in children is done by using the software that is installed on the smartphone using the image to speech. This method is expected to be more easily carried out and the results are expected to be maximum because of equipment smartphones today the price is very affordable and are often used by children ages two until three years old to play games.